PH-Responsive and pyrene based electrospun nanofibers for DNA adsorption and detection. Issue 10 (18th January 2017) - Yeh, Cheng-Ting; Chen, Ching-Yi
Abstract : A labeling-free DNA adsorption and detection method based on pH-responsive volume changes poly(DMAEMA- co -SA- co -Py) nanofibers shows its potential applications in DNA adsorption and separation. Abstract : A facile and labeling-free DNA adsorption and detection method is developed by pH-responsive and luminescent electrospun (ES) nanofiber mats fabricated using poly((2-(dimethylamino)ethyl methacrylate)- co -(stearyl acrylate)- co -((1-pyrene)methyl 2-methyl-2-propenoate)) (poly(DMAEMA- co -SA- co -Py)). FE-SEM images show the ES nanofibers have good wettability and integrity in aqueous solution with smooth and bead-free morphology. A decrease in the excimer-to-monomer fluorescent intensity ratio of pyrene moiety from pH 7 to pH 5 indicates a deswelling–swelling transition behavior due to protonation of DMAEMA segment. However, an obvious increase of excimer-to-monomer ratio is observed in the presence of DNA because of the electrostatic interaction between cationic fibers and negative charged phosphate groups from DNA. The detachment of DNA could be modulated by adjusting the pH value to 7. These results indicate this new ES nanofibrous mat has the potential applications for DNA adsorption, detection and separation.